Chemical characterization of the smallest S-nitrosothiol, HSNO; Cellular cross-talk of H2S and S-nitrosothiols - Filipovic, Milos; Miljkovic, Jan; Nauser, Thomas; Royzen, Maksim; Klos, Katharina; Shubina, Tatyana; Koppenol, Willem H.; Lippard, Stephen J.; Ivanovic-Burmazovic, Ivana (Journal of the American Chemical Society, 2012)
Dihydrogen sulfide recently emerged as a biological signaling molecule with important physiological roles and significant pharmacological potential. Chemically plausible explanations for its mechanisms of action have remained elusive, however. Here, we report that HS reacts with S-nitrosothiols to form thionitrous acid (HSNO), the smallest S-nitrosothiol. These results demonstrate that, at the cellular level, HSNO can be metabolized to afford NO, NO, and NO species, all of which have distinct physiological consequences of their own. We further show that HSNO can freely diffuse through membranes, facilitating transnitrosation of proteins such as hemoglobin. The data presented in this study explain some of the physiological effects ascribed to HS, but, more broadly, introduce a new signaling molecule, HSNO, and suggest that it may play a key role in cellular redox regulation. © 2012 American Chemical Society.